Green solvent engineering for enhanced performance and reproducibility in printed carbon-based mesoscopic perovskite solar cells and modules. Issue 2 (9th December 2021) - Worsley, C.; Raptis, D.; Meroni, S. M. P.; Patidar, R.; Pockett, A.; Dunlop, T.; Potts, S. J.; Bolton, R.; Charbonneau, C. M. E.; Carnie, M.; Jewell, E.; Watson, T.
Abstract : Green solvent mixes are applied in printed mesoscopic perovskite solar cells and modules, achieving 13.8% PCE at 1 cm 2 and >9% PCE in a 220 cm 2 module. This shows how green solvent engineering can aid improvement and scale-up in emerging technologies. Abstract : Mesoscopic carbon-based perovskite solar cells (CPSCs) are frequently described as a potential frontrunner for PSC commercialization. Previous work has introduced γ-valerolactone (GVL) as a sustainable, non-toxic, green alternative to GBL for CPSC perovskite precursors. In this work, methanol (MeOH) solvent additives are applied to enhance the performance and reproducibility of GVL-based precursors, through improving electrode wetting, infiltration, and perovskite crystal quality. Precursors incorporating 10% MeOH are found to substantially enhance reproducibility and performance, achieving a champion PCE of 13.82% in a 1 cm 2 device and >9% in a 220 cm 2 module fabricated in ambient conditions. Stability is also improved, with an unencapsulated MeOH device exhibiting a T80 of >420 hours at 50 °C in ambient humidity under continuous AM1.5 illumination. This work established GVL-based precursors as commercially attractive and provides an example of how green solvent engineering can be applied in the development, amelioration and scale-up of novel photovoltaics.